3-SURFACE TWISTORS AND CONFORMAL EMBEDDING - Tod, K (Kluwer Academic Publishers-Plenum Publishers, 1984)
The three-surface twistor equation is defined for an arbitrary three-surface Σ in an arbitrary curved space M. It is proved that three-surface twistors exist on 2 if and only if Σ can be embedded in a conformally flat space-time with the same first and second fundamental forms. © 1984 Plenum Publishing Corporation.